2009
DOI: 10.1002/chem.200901362
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Atom Abstraction Reactions by Manganese(V)– and Manganese(IV)–Oxo Porphyrin Complexes in Aqueous Solution

Abstract: High-valent manganese(IV or V)-oxo porphyrins are considered as reactive intermediates in the oxidation of organic substrates by manganese porphyrin catalysts. We have generated Mn(V)- and Mn(IV)-oxo porphyrins in basic aqueous solution and investigated their reactivities in C-H bond activation of hydrocarbons. We now report that Mn(V)- and Mn(IV)-oxo porphyrins are capable of activating C-H bonds of alkylaromatics, with the reactivity order of Mn(V)-oxo>Mn(IV)-oxo; the reactivity of a Mn(V)-oxo complex is 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
53
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 59 publications
12
53
2
Order By: Relevance
“…[35] On this basis, we propose that the reaction takes place via a rate determining hydrogen atom abstraction (HAT) that can be regarded as a proton coupled electron transfer (PCET), followed by a fast electron-transfer. [68, 76, 83, 84]…”
Section: Resultsmentioning
confidence: 99%
“…[35] On this basis, we propose that the reaction takes place via a rate determining hydrogen atom abstraction (HAT) that can be regarded as a proton coupled electron transfer (PCET), followed by a fast electron-transfer. [68, 76, 83, 84]…”
Section: Resultsmentioning
confidence: 99%
“…9 With regard to synthetic systems, Mn K-edge XAS has played a critical role in the characterization of high-valent oxo- and hydroxo-manganese species 10−16 that model intermediates commonly proposed in biological and synthetic oxidation reactions. 13,15,1722 Although several Mn V –oxo adducts have been structurally characterized by X-ray diffraction, 2326 Mn K-edge XAS has been commonly employed to determine metal–ligand bond lengths for high-valent oxo- and hydroxo-manganese adducts that have thus far eluded structural characterization by X-ray diffraction. 10−22,27 A major advantage of the XAS technique is that crystalline samples are not required.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Nonetheless, studying these effects on C–H bond activation or oxygen atom transfer is challenging due to limitations in accessing metal complexes with properties suitable for meaningful comparison. [2d,4] Such studies are even more challenging in multinuclear systems, which represent more accurate models of enzymes’ active sites. [1f,5] Only recently, a study of bimetallic complexes demonstrated that changing the oxidation state from [HO-Fe IV -O-Fe IV =O] to [HO-Fe III -O-Fe IV =O] resulted in a change in spin-state, concomitant with a remarkable million-fold increase in the rate of C–H bond cleavage.…”
mentioning
confidence: 99%